Analisis Nilai Moral pada Novel ”the Truth about Forever (Kebencian Membuatmu Kesepian)” Karya Orizuka - Komariyah, Siti; Ramdhani, Intan Sari (MASALIQ, 2022)
This research discusses the moral values contained in a novel entitled "the truth about forever". The purpose of this study is to expose moral values in the novel "the truth about forever" and the author hopes that readers can understand the content of the novel. The method used in this study is to use a descriptive method with a moral approach. After the author analyzes the novel "the truth about forever" in terms of moral aspects, the author can draw the conclusion that there are three aspects of moral values. . After the author analyzes the novel "the truth about forever" in terms of moral aspects, the author can draw the conclusion that there are three aspects of moral values. First, the manifestation of moral value in man's relationship with God (having faith and praying to God). Second, the indigo form of moral values in man's relationship with oneself (unselfishness, honesty, apologizing, admitting mistakes, self-awareness, promises, and regrets). Third, the manifestation of moral values in relation to humans with other human beings (advice between friends, parental affection for children, and affection between friends).